Analysis of the Influence of Social Media on Brand Awareness of MSMEs in Garut Regency - Herlianti, Anggun Oktavia; Gustari, Tresna Dita; Adiansyah, Adi; Isnawati, Isnawati; Fadilah, Azka Muhamad (Entrepreneurship Faculty, Universitas Garut, 2024)
The rapid development of social media has an impact on brand awareness among the community in MSMEs in Garut Regency. Social media can play an important role and provide benefits to the development of consumer awareness in people's consumer behavior. The purpose of this study is to identify social media analysis that can influence brand awareness of MSMEs in Garut. The research method of quantitative descriptive study, by analyzing the influence of social media on brand awareness of MSMEs in Garut, data collection techniques carried out through observation and questionnaires, data analysis techniques using validity tests, reliability and multiple linear regression. The results of the data analysis that have been carried out using analysis of the influence of social media on brand awareness in MSMEs in Garut Regency shows the importance of using social media platforms in building brand awareness, which can lead to increased sales and consumer loyalty. This active involvement is important for UMKM in Garut to be able to compete with larger and better-known products in the market. The results of the data analysis are interpreted that social media has an important role in supporting its influence on consumer awareness.